IMPLEMENTING SUSTAINABLE STRATEGIES: A CASE STUDY ANALYSIS OF THE SLOVENIAN BUSINESS ENVIRONMENT - Nuša Lazar (Agora International Journal of Economical Sciences, 2025)
A sustainable business strategy integrates economic, environmental, and social considerations into core operations, aiming for long-term value creation for both the organization and its stakeholders, while ensuring resource conservation. This paper examines the implementation of sustainable business strategies and compliance with European Sustainability Reporting Standards (ESRS) within the Slovenian business environment. It analyzes their content and strategic importance, particularly concerning evolving EU regulations. Employing a methodology that combines a review of relevant literature, analysis of the ESRS, and case study analysis of the Slovenian business environment the research investigates the current state of sustainability practices in Slovenia. The study examines a public initiative to boost Slovenian enterprises' international competitiveness via sustainable business transformation. Case studies showcase best practices in sustainable strategy implementation, emphasizing their critical role in maintaining competitiveness. Supported by national programs like SPIRIT Slovenia and the GZS Sustainability Chains, Slovenian companies are increasingly adopting these practices, reflecting global trends and leveraging local opportunities.